Argon plasma effects on maize: pesticide degradation and quality changes. (14th June 2019) - Feng, Xinxin; Ma, Xin; Liu, Hongxia; Xie, Jinzhuo; He, Chi; Fan, Rui
Abstract: BACKGROUND: During planting, storage and transportation of maize excessive amounts of pesticides are used to ensure production, resulting in pesticide residues on the maize that can threaten human health. Plasma, compared with other technologies, has been widely regarded as a green, safe and promising technology for surface decontamination to ensure maize safety and quality. RESULTS: The aim of this study is to discuss plasma effects on the degradation of chlorpyrifos and carbaryl on maize surface and the changes of treated maize quality. Results achieved the largest degradation efficiency of chlorpyrifos and carbaryl, up to 91.5% and 73.1%, respectively. The physical changes of maize were observed by scanning electron microscopy (SEM), showing a decrease in contact angle, an increase in surface free energy and polar component, leading to improved hydrophilicity of the treated maize. There was no significant change of vitamin B2 content of maize. A significant increase of acid value and decrease of moisture content and starch content were observed within acceptable limits. CONCLUSION: It is reasonable to believe that argon plasma treatment enhances the edible safety of maize while maintaining maize quality. © 2019 Society of Chemical Industry